TITANITE OF THE VISHNEVOGORSKY ALKALINE COMPLEX (South Ural) - V.A. Popov (Минералогия)
Titanite CaTi(SiO4 )O is a common accessory mineral of alkaline rocks and pegmatites of the Vishnevogorsky alkaline complex, South Urals. It occurs in many magmatic assemblages, is found in some metasomatites, underwent deformation and recrystallization. Titanite is characterized by zonal-sectorial structure, various habit, color and composition and exhibits twins along {100} and monocrystals with forms of {110}, {111}, {100}, {001}, and { 1 11}. It contains high amount of Nb, Na, Al, Fe, V, and REE. In some ore types (zone 125), abundant titanite hampers concentration of pyrochlore concentrates.